Transfer Of antibiotic resistance gene CTX-M- An alarm for the clinician (Bangladesh Journal of Medical Microbiology, 2013)
No AbstractDOI: http://dx.doi.org/10.3329/bjmm.v5i2.16416 Bangladesh J Med Microbiol 2011; 05 (02): 2-5